Stewardship and beyond? Young people’s lived experience of conservation activities in school grounds - Ruck, Andy; Mannion, Greg (Environmental Education Research, 2021)
This article provides ethnographic insight into the more-than-human relationships enacted through young people’s participation in school grounds conservation activities. As a response to the escalating biodiversity crisis, conservation appears well-placed to facilitate young people’s development of an environmental ethic of care, and a capacity to work towards addressing environmental issues. Proponents of posthuman pedagogies, however, argue that the ‘stewardship’ perspective underlying these activities fails to achieve the radical shift in human-environment relations required in response to the Anthropocene, given its apparent reinforcement of a perceived human/nature binary, and narrow ‘solutions’-based approach. Considering these critiques, this article demonstrates that where there is openness to unplanned more-than-human encounters and the enactment of young people’s own ‘lived curricula’, conservation activities can nonetheless enable forms of ‘collective thinking with the more-than-human world’ that transcend any underlying ‘stewardship’ perspective. We therefore point to the potential role of conservation activities within posthuman responses to the Anthropocene, provided such openness is maintained.
Publisher: Routledge _eprint: https://doi.org/10.1080/13504622.2021.1964439
Keywords: Conservation; anthropocene; more-than-human; posthuman; school grounds; stewardship